İflasın Ertelenmesi ve Borca Batıklık: Bir Uygulama - Otlu, Fikret; İşleyen, Şakir; Kaya, Hamza (Muş Alparslan Üniversitesi, 2019)
Thepostponement of bankruptcy is the legal protection for the associations andfinancial companies which are overindepted and are highly-likely to berecovered that companies present reliable forecasts, include convincing andserious betterment project to be saved. The legal situation of overindeptednessis assets of the company which could not fulfill the payments to debate even byevaluating assets according to their real value (potential selling value) –opposite to evaluating according to annual financial statement which evaluatesthem according to book value – so the company cannot fulfill the commitmentsand debts. In this study with the title of “The Postponement of Bankruptcy andOverindeptedness: An Application”; bankruptcy, postponement of bankruptcy, terms of postponement of bankruptcy and overindeptedness are being approachedby examining a Van’s company’s demand of postponement of bankruptcy and issuingan overindeptedness balance sheet for them to evaluate their works.

İflasınertelenmesi, borca batık durumda bulunan, şirket tarafından sunulan; somutöngörüler içeren, ciddi ve inandırıcı bir iyileştirme projesi çerçevesinde budurumdan kurtulması kuvvetle muhtemel bulunan kooperatiflerle sermayeşirketleri için öngörülmüş bir hukuki korunma yoludur. Borca batıklık iseşirket aktifleri -yıllık bilançoda olduğu gibi defter değerleriyle değil- fakatgerçek (olası satış değerleri) değerleriyle değerlemeye tabi tutulsalar bilealacaklıların, alacaklarını alamamaları, yani şirketin borç ve taahhütlerinikarşılayamaması durumudur. “İflasın Ertelenmesi ve Borca Batıklık: BirUygulama” başlıklı bu çalışmada, genel olarak iflas, iflasın ertelenmesi, iflasın ertelenmesinin şartları ve borca batıklık konuları ele alınarak Vanilinde iflas erteleme talebinde bulunan bir şirketin borca batıklık bilançosudüzenlenerek, değerlendirilmiştir.
The Postponement of Bankruptcy and Overindeptedness: An Application
anemon
Keywords: Bankruptcy; Postponement of Bankruptcy; Overindeptedness; İflas; İflasın Ertelenmesi; Borca Batıklık